THE EFFECT OF RETURN ON ASSETS, FIRM SIZE, AND FINANCING TO DEPOSIT RATIO ON THE STOCK PRICE OF PT. BRI SHARIA, TBK. - Dadang Husen Sobana (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
The stock price of PT BRI Shariah TBK since carrying out the IPO has continued to appreciate to 120 per cent, first the decision to merge three state-owned sharia banks into one Indonesian sharia bank in the last quarter of 2020. This study aims to analyze the various factors that affect the share price of PT BRI Shariah TBK during 2019-2020 based on ROE, Company Size, and FDR as variables that were thought to influence it. The study uses a descriptive method with a quantitative approach. The study uses secondary data obtained from the monthly publication reports and the monthly share price of PT. BRI Shariah, TBK, accessed from Yahoo Finance. Data analysis using multiple regression analysis, where the processing uses E-views 9 software. This study concludes that simultaneously ROE, Firm Size, and FDR have a significant effect on the stock price of PT. BRI Shariah TBK, Then partially ROE and FDR have a significant effect on the stock price of PT. BRI Shariah TBK in 2019 and 2020.